ERS/ESTS/EACTS/ESTRO guidelines for the management of malignant pleural mesothelioma. Issue 6 (11th June 2020) - Scherpereel, Arnaud; Opitz, Isabelle; Berghmans, Thierry; Psallidas, Ioannis; Glatzer, Markus; Rigau, David; Astoul, Philippe; Bölükbas, Servet; Boyd, Jeanette; Coolen, Johan; De Bondt, Charlotte; De Ruysscher, Dirk; et al.
The European Respiratory Society (ERS)/European Society of Thoracic Surgeons (ESTS)/European Association for Cardio-Thoracic Surgery (EACTS)/European Society for Radiotherapy and Oncology (ESTRO) task force brought together experts to update previous 2009 ERS/ESTS guidelines on management of malignant pleural mesothelioma (MPM), a rare cancer with globally poor outcome, after a systematic review of the 2009–2018 literature. The evidence was appraised using the Grading of Recommendations, Assessment, Development and Evaluation approach. The evidence syntheses were discussed and recommendations formulated by this multidisciplinary group of experts. Diagnosis: pleural biopsies remain the gold standard to confirm the diagnosis, usually obtained by thoracoscopy but occasionally via image-guided percutaneous needle biopsy in cases of pleural symphysis or poor performance status. Pathology: standard staining procedures are insufficient in ∼10% of cases, justifying the use of specific markers, including BAP-1 and CDKN2A ( p16 ) for the separation of atypical mesothelial proliferation from MPM. Staging: in the absence of a uniform, robust and validated staging system, we advise using the most recent 2016 8th TNM (tumour, node, metastasis) classification, with an algorithm for pre-therapeutic assessment. Monitoring: patient's performance status, histological subtype and tumour volume are the main prognostic factors of clinical importance in routine MPM management. Other potential parameters should be recorded at baseline and reported in clinical trials. Treatment: (chemo)therapy has limited efficacy in MPM patients and only selected patients are candidates for radical surgery. New promising targeted therapies, immunotherapies and strategies have been reviewed. Because of limited data on the best combination treatment, we emphasise that patients who are considered candidates for a multimodal approach, including radical surgery, should be treated as part of clinical trials in MPM-dedicated centres. A European expert task force proposes updated and practical guidelines on routine management of malignant pleural mesothelioma, after a systematic review of the 2009–2018 literature (GRADE), including new promising therapies and strategies http://bit.ly/38876ta